Laparoscopic Omentopexy, Rectus Sheath Tunneling and Implantation of the Peritoneal Dialysis Catheter Using a Peritoneal Dialysis Port. Issue 3 (May 2018) - Keramati, Mohammad Reza; Abbaszadeh-Kasbi, Ali; Keshvari, Amir
Background: Prophylactic laparoscopic omentopexy is a safe technique to prevent peritoneal dialysis (PD) catheter obstruction. For the first time, we would like to describe a surgical technique in which the omentopexy is done using a single PD port which is used for the omentopexy, PD catheter insertion, and the rectus sheath tunneling of the catheter. Methods: The surgical method of the omentopexy using the PD port (US Patent 20170119430) will be thoroughly described. To evaluate the surgical method, we performed the procedure in 15 consecutive patients with chronic renal failure and followed up the patients. Results: No intraoperative complication was observed. During the follow-up period, catheter flow failure due to omental wrapping was found in none of the patients. No other complication including exit-site infection, peritonitis, or catheter leakage was detected. Conclusion: Using this technique the catheter can not only be implanted through a proper and long rectus sheath, but the omentopexy can also be done without an additional port. This can reduce port-site complications and dialysis fluid leakage.